1999
DOI: 10.1007/bf02345892
|View full text |Cite
|
Sign up to set email alerts
|

Improved method for the separation of radioactive strontium from various samples by mixed solvent anion exchange

Abstract: Procedures tbr the separation and determination of 9~ in liquid samples, with cation and anion exchangers have been described. Strontium, yttrium and other cations bind to the cation exchanger and are eluted from the column by means of nitric acid. Separation of yttrium and strontium from other cations is carried out on columns filled with strong base anion exchangers in nitrate form with alcoholic solutions of nitric acid. This separation method enables the determination of 9~ through yttrium on a low-level g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…The recovery of strontium in all cases was about 98%. This result is similar to other study with different anion exchangers [13,14,17].…”
Section: A Study On the Removal Of Calcium From Sample Solution Using Anion Exchange Chromatographysupporting
confidence: 93%
See 3 more Smart Citations
“…The recovery of strontium in all cases was about 98%. This result is similar to other study with different anion exchangers [13,14,17].…”
Section: A Study On the Removal Of Calcium From Sample Solution Using Anion Exchange Chromatographysupporting
confidence: 93%
“…Previous report in literature [17] showed that the distribution constant of calcium on anionic exchanger much lower than that of strontium in alcoholic medium. Several cations can adsorb on strong base anion exchange resins, which contain the quaternary ammonium group with nitrate as counter-ion from solutions of nitric acid in alcohol [14] and the order of adsorption of these cations depends on the distribution coefficients [13,14]. The phenomenon of adsorbed cations on anionic exchangers can only be obtained in solutions with highly polarized alcohol [17].…”
Section: A Study On the Removal Of Calcium From Sample Solution Using Anion Exchange Chromatographymentioning
confidence: 99%
See 2 more Smart Citations
“…A lot of work has been done to find simpler, faster and more accurate methods. Nowadays, extraction chromatographic resin has been developed for isolation of radionuclides from various kinds of matrix [10][11][12][13]. In China, the conventional EC method for analyzing strontium-90 in crops is based on the GB11222.1 − 89 [14] which uses ion-exchange resin with di (2-ethylhexyl) phosphoric acid (HEDHP) to isolate Y-90, counting Y-90 with lowbackground proportional counter, and then the radioactivity of Sr-90 can be evaluated.…”
Section: Introductionmentioning
confidence: 99%